2008
DOI: 10.1051/vetres:2008055
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophils as one of the major haptoglobin sources in mastitis affected milk

Abstract: The antioxidant haptoglobin (Hp) is an acute-phase protein responsive to infectious and inflammatory diseases. Hp and somatic cell counts (SCC) are sharply elevated in bovine milk following intramammary administration of endotoxin or bacteria. However, the sources of milk Hp responsible for such increases are not fully understood. The purpose of this study was to define the source of milk Hp from dairy cows with naturally occurring mastitis. Quarter milk samples selected from 50 dairy cows were separated into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 32 publications
4
34
0
6
Order By: Relevance
“…These neutrophils are then attributed for the release of Hp into the plasma shown in our study. A similar study was conducted by us in cows with mastitis, large accumulation of neutrophils in mammary glands resulted in a marked Hp increase in milk (Lai et al, 2009). We suggest that neutrophils are responsible for the elevated Hp levels in plasma following the exercise.…”
Section: Hp Mrna Levels Of Liver Remaining Unchanged In Mice After Exsupporting
confidence: 83%
“…These neutrophils are then attributed for the release of Hp into the plasma shown in our study. A similar study was conducted by us in cows with mastitis, large accumulation of neutrophils in mammary glands resulted in a marked Hp increase in milk (Lai et al, 2009). We suggest that neutrophils are responsible for the elevated Hp levels in plasma following the exercise.…”
Section: Hp Mrna Levels Of Liver Remaining Unchanged In Mice After Exsupporting
confidence: 83%
“…Lactotransferrin is an iron-binding protein mainly synthesized by MECs and, to a lesser extent, by neutrophils (47), having antibacterial, immune-modulating, antiinflammatory, and antioxidant activity (48,49). Haptoglobin is found to be increased in plasma and in milk in clinical mastitis and in chronic subclinical mastitis, together with amyloid protein A (24), and several studies indicated that one of the main sources of these two proteins in milk might be MECs (50)(51)(52). S100A9 and S100A8 are mainly expressed in the cytoplasm of neutrophils and monocytes but also in activated endothelial and epithelial cells (53)(54)(55)(56)(57)(58)(59).…”
Section: Discussionmentioning
confidence: 99%
“…However, in MC the mRNA expression was still elevated during disease in our experiments. In this case the mammary epithelial cells might be an additional source of HP mRNA [49]. In mammary tissue HP mRNA expression was also found to be increased during mastitis [50].…”
Section: Discussionmentioning
confidence: 85%